Communication in Employee Productivity in Transportation Service Companies: Komunikasi dalam Produktivitas Kerja Karyawan pada Perusahaan Layanan Transportasi - Dicky Aditya Septyawan; Hasan Ubaidillah (Academia Open, 2023)
The purpose of this study is to know the communication in employee productivity. The company was examined by the author a company engaged in the field of providing goods delivery services. This research is a type of descriptive using quantitative methods. Data retrieval techniques are spreading questionnaires to 50 respondents who are employees of the driver at PT Djuta Cross Nusa. Analysis techniques that use the SPSS program (statistical program for social science) version 21 for Windows. The results of this study, namely communication have an important influence on the achievement of the success of the company, namely between employees of Driver and PT Duta cross Nusa. Highlights: Communication significantly impacts employee productivity in goods delivery services. Effective communication enhances the success of the company, particularly between drivers and PT Djuta Cross Nusa. Understanding the role of communication can lead to improved performance and operational efficiency in the delivery services industry. Keywords: Communication, Employee productivity, Goods delivery services, Descriptive study, PT Djuta Cross Nusa.